Influence of Gender and Age on the Incidence of Dengue Haemorrhagic Fever (DHF) in Bandar Lampung City - Anisa Viola Pitaloka; Cahyati, Widya Hary; Wijayanti, Yuni (Public Health Perspective Journal, 2025)
Gender and age are one of the factors that can affect dengue disease. Many cases occur in the community with an age range of 15-45 years. Males are often found because they have activities outside the home when the vector that causes DHF is actively biting during the day. The number of DHF patients in Bandar Lampung City in 2022 was 1,440 patients, having an IR of 130.1 per 100,000 population. The number of cases has increased from 2021, which was 623 patients with an IR of 57.2 per 100,000 population. The purpose of this study was to determine the effect of gender and age on the incidence of DHF in Bandar Lampung City. This study used a case control design and used the chi square test. By using a sampling technique that is using Stratified Random Sampling. To calculate the sample in each section using the Proportionate Stratified Random Sampling technique. This research tool uses questionnaire sheets and checklist sheets. The population of this study were DHF patients in 2022 in Bandar Lampung City. The research sample was 154 respondents with 77 cases and 77 controls. There was no influence between gender (p=1.000) on the incidence of DHF in Bandar Lampung City. There was an effect of age (p=0.000, OR=5,211) on the incidence of DHF in Bandar Lampung City.